EVALUATION OF THE CO-INFECTION CAUSED BY SWINE CIRCOVIRUS 2 AND Mycoplasma hyopneumoniae IN LUNG SAMPLES OBTAINED FROM A SLAUGHTERHOUSE IN THE MATA MINEIRA REGION, BRAZIL / Avaliação da coinfecção do circovírus suíno 2 com Mycoplasma hyopneumoniae em ... - BEZERRIL, J. E.; MACHADO, J. P.; SILVA, F. M. F.; BULOS, L. H. S.; VILORIA, M. I. V.; ALMEIDA, M. R. (Ars Veterinaria, 2012)
E<span style="font-size: 10pt; color: black; font-family: "Times New Roman","serif"; mso-ansi-language: PT; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="PT">ste trabalho teve como objetivo<span style="font-size: 10pt; color: red; font-family: "Times New Roman","serif"; mso-ansi-language: PT; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="PT"> <span style="font-size: 10pt; color: black; font-family: "Times New Roman","serif"; mso-ansi-language: PT; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="PT">pesquisar a associação do PCV2 e M. Hyopneumoneae em amostras de pulmão de suínos. 32 fragmentos de pulmões, sendo 16 com lesões macroscópicas (CLM) e 16 sem lesões macroscópicas (SLM) foram analisados pela histopatologia, pelo teste de imuno-histoquímica (IHC) e pela reação de polimerase em cadeia em tempo real (qPCR). Não foi observada correlação positiva entre a histopatologia e a imuno-histoquímica. Não houve também, correlação positiva entre número de amostras com lesões características de pneumonia viral e a carga viral de PCV2 medida por qPCR. Analisando os dados obtidos da detecção dos agentes e lesões microscópicas associadas, constatou-se que em 4 amostras analisadas (12,5%) houve uma co-infecção entre o PCV2 e M. Hyopneumoneae. Este resultado demonstra uma possível associação deste dois agentes. Novos estudos deverão ser realizados para determinação de outros possíveis patógenos envolvidos na patogenia da PRDC na região da Zona da Mata Mineira. SUMMARY <span style="font-size: 10pt; color: black; font-family: "Times New Roman","serif"; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">The aim of this study was determine the association between PCV2 and M. Hyopneumoneae in pig lung samples. Thirty two lung fragments, from which 16 had macroscopic lesions (CLM) and the other 16 had no macroscopic lesions (SLM), were analyzed by histopathology, immunohistochemistry assays and polymerase chain reaction in real time (qPCR). No positive correlation was observed among the histology and the immunohistochemistry assay (IHC). There was also no positive correlation between the number of samples with viral pneumonia type of lesions and PCV2 viral load measured by qPCR. Analysis of the data obtained by detection of agents and associated microscopic findings showed that PCV2 and M. Hyopneumoneae co-infection was found in four samples (12,5%). This result reveals a possible association of these two agents. Further studies are required to determine additional potential pathogens involved in the pathogenesis of the PRDC in the Mata Mineira region, Brazil.